A prophet in his country - Lucian CHIȘU (Diversitate si Identitate Culturala in Europa)
This text is a tribute to the academician Eugen Simion, on his 85th birthday. A former president of the Romanian Academy (1998 – 2006), member of academic societies in France, Denmark, Moldova, university professor, literary critic and historian, editor, essayist, he is still more active than ever and his achievements are brimming over with energy and youthful enthusiasm. The intellectual merits of the humanist Eugen Simion place him in the gallery of encyclopaedic personalities of culture worldwide.